1997
DOI: 10.1161/01.atv.17.6.1114
|View full text |Cite
|
Sign up to set email alerts
|

Relation of High TG–Low HDL Cholesterol and LDL Cholesterol to the Incidence of Ischemic Heart Disease

Abstract: High triglyceride (TG) and low HDL cholesterol (HDL-C) is the characteristic dyslipidemia seen in insulin-resistant subjects. We examined the role of this dyslipidemia as a risk factor of ischemic heart disease (IHD) compared with that of high LDL cholesterol (LDL-C) in the Copenhagen Male Study. In total 2910 white men, aged 53 to 74 years, free of cardiovascular disease at baseline, were subdivided into four groups on the basis of fasting concentrations of serum TG, HDL-C, and LDL-C. "High TG-low HDL-C" was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
159
1
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(180 citation statements)
references
References 28 publications
15
159
1
5
Order By: Relevance
“…Additionally, transfer of TG from TG-rich lipoproteins to HDL-c is done using this enzyme in exchange for cholesteryl esters, and that's why a negative correlation between these two variables can be found according to CETP activity (26). HDL-c and TG are considered important risk factors for CVD (27,28) and these correlations can be important. Moreover, BMI and waist circumference are considered the markers of adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, transfer of TG from TG-rich lipoproteins to HDL-c is done using this enzyme in exchange for cholesteryl esters, and that's why a negative correlation between these two variables can be found according to CETP activity (26). HDL-c and TG are considered important risk factors for CVD (27,28) and these correlations can be important. Moreover, BMI and waist circumference are considered the markers of adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…a Quintile ranges for general population of men aged 20-39 are used Statistical significance levels : * p < 0.05, * * p < 0.01, * * * p < 0.001 vs non-drinkers procedure for HDL-C was standardized more easily than that for TG, HDL-C had long been used as a parameter taking the place of TG in practice in the lipid clinic, while the use of TG in judging the appropriateness of the treatment of hyperlipidemia has long been ignored in epidemiological studies (23). Since evidence has accumulated over the past ten years showing the importance of TG as an independent risk factor in CAD (24)(25)(26)(27), it seems necessary to reexamine the change in lipid parameters with respect to life style in a population-based epidemiological study and to reevaluate the significance of HDL-C and TG as possible risk factors in CAD. It is well known that obesity and serum TG are the most important factors in the decrease of HDL-C (13-16).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of the epidemiological data (43,44), in addition to the data obtained in clinical studies (25)(26)(27) have shown that TG is an independent cardiovascular risk factor. A report from the PROCAM study also showed that high triglyceride was a risk even in a population with high HDL-C (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because TG values fluctuate markedly after meals and [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] the assay procedure for HDL-C was standardized more easily than that for TG, HDL-C has long been used as a parameter, taking the place of TG in practice in the clinic and the use of TG in judging the appropriateness of the treatment of hyperlipidemia has long been ignored in epidemiological studies (25). However, meta-analysis of epidemiological data (26,27) has shown that TG is an independent cardiovascular risk factor and evidence has accumulated over the past ten years showing the importance of TG as an independent risk factor in CAD (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%